Blood trace elements in association with esophageal squamous cell carcinoma risk, aggressiveness and prognosis in a high incidence region of China - Shuyi Qiu; Bingmeng Xie; Jiahui Liao; Jianan Luo; Xi Liu; Lihua He; Yiteng Huang; Lin Peng (Scientific Reports)
Abstract Toxic elements exposure and imbalance in essential element homeostasis remain incomprehensive in esophageal squamous cell carcinoma (ESCC) carcinogenesis, especially in tumor progression. To reveal the toxic and essential elements inside body associated with ESCC occurrence, aggressive features and outcomes, whole blood concentrations of eight trace elements were quantified in 150 ESCC cases and 177 controls using inductively coupled plasma-mass spectrometry (ICP-MS). Concentrations of cadmium (Cd), lead (Pb), chromium (Cr), copper (Cu), arsenic (As), and selenium (Se) showed significant differences between the case and control subjects. The restricted cubic spline (RCS) analysis showed As, Zinc (Zn), and manganese (Mn) was linked with ESCC risk in a U-shaped pattern, whereas an inverted U-shaped curve for Cd (all P-non-linear < 0.05). Contrary to Se, the elements Pb, Cr and Cu were positively associated with ESCC risk. By Bayesian Kernel Machine Regression models, the mixtures of the eight trace elements were found to be significantly associated with ESCC risk and metastasis, with Cr, Mn, Cu, Zn, and Pb having a PIP of 1.000 for occurrence risk and Mn being the main contributor for metastatic risk (PIP = .6570). The weighted quantile sum (WQS) model consistently showed that Cu, Cr, Pb, and Cd ranked as the top four positive elements for ESCC risk. Multivariable logistic regression analysis indicated Pb and As were positively associated with tumor invasion (adjusted OR 3.024 [1.053–8.689]; OR 4.385 [1.271–15.126], respectively), whereas Se had the opposite trend (adjusted OR 0.261 [0.074–0.927). Patients with high Cr, Mn, or Pb showed worse overall survival (OS), and high Mn were linked to inferior progression-free survival (PFS) (all P < 0.05). Zn and Pb, and Mn and Cu were identified as independent prognostic factors for OS and PFS, respectively. This study suggests trace element disbalance in human body contributes to the risk of onset and progression of ESCC, especially in a high-incidence region. Further epidemiological and experimental studies were needed to clarify the probable pathogenic processes underpinning the potential link between trace element mixtures and ESCC.